Analysis of Wear Process in Aeronautic Spur Gear - Chen Haifeng; Tang Jinyuan; Zhou Weihua (Jixie chuandong, 2018)
Aiming at the problem of wear on the spur gear of a type reducer,by the confocal laser scanning microscope,white light interferometer,the surface microtopography and microhardness of the gear are detected. The test results indicate that the surface of driven gear has irregular texture after nitriding,and surface roughness Ra is reached 0. 87 μm. The microhardness value of the driven is higher than the driving. The surface of driving has obvious pits and the surface roughness Ra is 0. 50 μm. According to test results,the main reason for the wear of driving surface is quite serious is that,the surface roughness and microhardness of the driven and driving not match either,the Abbott curve of the driven is superior to the driving.